Mechanism of Building Block Exchange in Stacks of Self-Replicating Macrocycles - Mattia, Elio; Pal, Asish; Leonetti, Giulia; Otto, Sijbren (Synlett, 2017)
Self-replicating molecules containing labile reversible covalent bonds are becoming increasingly topical. Yet their robustness to component exchange and the threat of loss of information has received very little attention. We show here that supramolecular interactions can efficiently protect self-replicating molecules from otherwise rapid component exchange.
Keywords: self-replication; self-assembly; exchange; supramolecular polymers; dynamic combinatorial chemistry; systems chemistry